The response to shock loads of Ni-MOF and NiO NPs on aerobic granular sludge and algal-bacterial aerobic granular sludge - Alfonz Kedves; Çağdaş Yavuz; Orsolya Kedves; Henrik Haspel; Zoltán Kónya (Heliyon)
Currently, the increasing use of nickel metal-organic frameworks (Ni-MOF) and nickel oxide nanoparticles (NiO NPs) has raised concerns regarding their potential environmental impact on wastewater treatment systems. Herein, the responses of aerobic granular sludge (AGS) and algal-bacterial aerobic granular sludge (AB-AGS) to Ni-MOF and NiO NPs were investigated. The results showed that Ni-MOF concentrations of 50, 100, and 200 mg/L significantly reduced nutrient removal in both systems, particularly affecting ammonia, nitrite, and phosphorus removal, while denitrification processes remained stable. AB-AGS exhibited greater tolerance to nickel than AGS, likely due to its higher content of extracellular polymeric substances (EPSs), in which the algae were embedded, indicating a robust bacterial-algal symbiotic system. Conversely, NiO NPs had no adverse effects on bioreactor performance, likely due to their insolubility and integration into the sludge matrix. This research provides valuable insights into the potential future applications of AGS and AB-AGS technologies for treating wastewater contaminated with nickel and other heavy metals, highlighting the superior resilience of AB-AGS to nickel exposure.